Pelatihan Bantuan Hidup Dasar (BHD) Bagi Masyarakat Umum - Setyawati, Retno (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Cardiac arrest is a medical emergency that can cause death within minutes if not treated immediately. Basic Life Support (BLS) is a series of simple actions anyone can perform to maintain life until further medical attention is available. BLS knowledge and skills are essential for the general public to improve the survival rate of victims of cardiac arrest outside the hospital. This community service activity aims to improve the general public's ability to perform BLS. Implementation methods include interactive lectures, demonstrations, and hands-on practice of Cardiopulmonary Resuscitation (CPR) and the use of an Automated External Defibrillator (AED). Forty residents from various backgrounds participated in the activity, held at Village Hall X in June 2025. Evaluation results showed an increase in participant knowledge from 20% in the good category in the pre-test to 90% in the post-test, and CPR practical skills improved, with 85% of participants able to perform BLS steps correctly. BLS training effectively increases community preparedness in managing cardiac arrest outside a health facility.